Social Tariff Concessions and the Price Elasticity of Demand of Local Public Transport System in a Medium Sized Urban Area - Vietze, Christoph (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
The aim of the study is to calculate the price elasticity of demand for several local public transport products of a mid-sized German city (Jena) to estimate the potential subsidy requirements of social tariff concessions. The results of the ten year time series AR-model estimation show an elasticity coefficient of − 0.63 for a single ticket which is slightly higher in absolute terms compared with past studies but can be explained with the geographical structure of the examined city. The price elasticity of social concession-tariffs is significantly higher. This means that the income effect will be outweighed by the effect of lower demand of welfare recipients for (relatively inelastic) intra-city commuting.